2020
DOI: 10.37506/ijfmt.v14i3.10783
|View full text |Cite
|
Sign up to set email alerts
|

Study of Analytical Characterization and Antibacterial Activity of Silver Nanoparticles Synthesized by Using Pineapple Juice as a Reducing Agent

Abstract: In the past years, various phytosynthetic processes have been utilised of silver nanoparticles for the low cost and environmentally friendly comparing to the chemical and physical methods. These unique metal nanoparticles are used in several applications which are including pharmaceuticals, antimicrobial and biomedical applications. Wherefore, the object of this work is biosynthesizing AgNPs from extracts of pineapple juice as reducing studying their characteristics by Ultraviolet-Visible (UV-vis) Spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The REMA results showed that the MIC of the MnO NPs for the selected isolates was 12.5 U/mL. Many studies indicated that metal oxide NPs have achieved substantial attention because their antibacterial activity is based on their small size, which gives them the ability to penetrate bacteria and cause damage and toxicity to intracellular parts [ 16 , [28] , [29] , [30] , [31] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The REMA results showed that the MIC of the MnO NPs for the selected isolates was 12.5 U/mL. Many studies indicated that metal oxide NPs have achieved substantial attention because their antibacterial activity is based on their small size, which gives them the ability to penetrate bacteria and cause damage and toxicity to intracellular parts [ 16 , [28] , [29] , [30] , [31] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%